Vocational Curriculum Implementation of the Three Years Program of Electronics Engineering - Lipur Sugiyanta; Moch Sukardjo; M. Khairudin; Irdayanti Mat Nashir (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
This study analysed the implementation of the Indonesian Qualification Framework based vocational curriculum in the three years program of an electronics engineering, Faculty of Engineering, Universitas Negeri Jakarta. The analysis was focused on lecturers and students’ views. This evaluation used the model of Context, Input, Process, Product by involving 49 students in the 3rd semester, 6 lecturers, and administration staff. The findings showed that the implemented learning activities using the new curriculum paradigm are reliable. The context analysis indicated the correlation between lecturers’ competence and qualification and the goals of the study program. The input analysis showed that the lecturer's assignment was appropriate and correspond with lecturers’ subject and education background. The process analysis revealed that the learning process was in accordance with the lectures’ planning. In addition, the practicum activities were reportedly consistent with the academic calendar. The product analysis, in the form of courses distribution each semester, suggested that the needs for improvement to fit the new curriculum paradigm design.